High Li+ Conductivity of Li1.3+xAl0.3−xMgxTi1.7(PO4)3 with Hybrid Solid Electrolytes for Solid-State Lithium Batteries - Kim, Haena; Shaik, Mahammad Rafi; Kim, Sukju; Park, Yong Min; Jeon, Dong Won; Cho, Sung Beom; Choi, Sungho; Im, Won Bin (International Journal of Energy Research, 2024)
Solid-state electrolytes (SSEs) are promising future power sources for electronic vehicles (EVs) and devices due to their enhanced safety features, high energy density, and nonflammability. The NASICON structure has emerged as a frontrunner in oxide-based electrolytes, boasting high Li-ion conductivity and air stability. Nevertheless, developing high-performance oxide-based electrolytes remains challenging due to their inherently hard and brittle nature, presenting obstacles to achieving an optimal interface between the cathode and anode. In this study, to overcome this issue and enhance electrochemical stability and Li-ion conductivity, a new approach employing a hybrid solid electrolyte amalgamating polymer electrolytes with inorganic Li1.3+xAl0.3−xMgxTi1.7(PO4)3 powder (x = 0, 0.015, 0.030, 0.045, and 0.060) was investigated. Notably, employing nanosized Li1.3Al0.3Ti1.7(PO4)3 (LATP) synthesized via the sol-gel method led to a remarkable increase in ionic conductivity to 7.29 × 10-4 S cm-1, which was attributed to enhanced pellet density. Electrochemical analysis revealed that Li1.345Al0.255Mg0.045Ti1.7(PO4)3 exhibited superior specific capacity, stable high current density performance, and capacity recoverability compared to LATP. This pioneering study highlights the potential of hybrid solid electrolytes incorporating Mg-doped LATP as a promising material for practical solid-state lithium batteries.
Keywords: Electronic vehicles; Electronics devices; Hybrid solids; Li +; Li ion conductivities; Performance; Power sources; Safety features; Solid-state electrolyte; Solid-state lithium batteries